A New Clinical Classification for Gynecomastia Management and Predictive Outcome - Punia, Sudhanshu; Gupta, Amit (Indian Journal of Plastic Surgery, 2023)
Aim and objectives The aim of this study is to propose a new clinical classification for gynecomastia management based on our experience.Introduction We believe that the prevalent gynecomastia classifications need to be more detailed. Several key aspects that we noticed have either been incompletely represented or not mentioned at all, leaving them unclassified.Materials and Methods This study was conducted at the authors' center over 24 months from May 2020 to May 2022, and included 1,571 patients who were classified and treated as per our new classifications and small iterations were done to strengthen the classification.Results We were able to better classify our patients and previously unclassified situations. Skin sagging or a potential for skin sagging and puffy nipples were managed better. This classification allowed recommendation of each step of the procedure, resulting in high patient satisfaction, as all problem areas were sorted and outcome that was explained to them preoperatively was clearly visible postoperatively.Conclusion The new clinical classification for gynecomastia is a simple, clinical, straightforward, comprehensive, grading system, the use of which has helped the authors and the team in achieving precise and predictable results while ensuring patient satisfaction.
Keywords: gynecomastia; gynecomastia classification; puffy nipple; male breast enlargement.